“Extreme Left and Extreme Right Nationalistic Rhetoric Compared: Stage Left.” - Cunha, C. (ECPR Joint Sessions/session #25 “The Left(s) and nationalism(s)”, 2022)
This paper focuses on the two largest extreme-left parties’ (Portuguese Communist Party’s [PCP] and Left Bloc [Bloco de Esquerda-BE]) nationalistic rhetoric in Portugal. The nationalistic emphasis in this paper is not based on minority nationalist tendencies, given that Portugal is substantially homogeneous in ethnicity, but instead on nationalist arguments that emphasize the interests of the Portuguese rather than global capitalist interests or regional integration such as the European Union. The Portuguese Communist Party’s (PCP) historical nationalistic rhetoric, regularly seen in its Euroscepticism, will be analyzed. The PCP is interesting given its historically strong nationalist rhetoric despite its Marxist internationalism. Nationalistic arguments presented by the left libertarian Left Bloc (Bloco de Esquerda) will also be comparatively analyzed.